STUDY OF DISTINGUISHING FEATURES OF PAKISTANI STANDARD ENGLISH - Ali, Ameer; Samoon, Abdul Wahid; Ali, Mansoor (Elite : English and Literature Journal, 2020)
The current research has adopted a qualitative approach to investigate the linguistic differences of Pakistani Standard English in contrast to British Standard English. We studied morphological, lexical, and hybrid characteristics of Pakistani Standard English. Besides, we investigated the linguistic features to prove the fact that cultural context determines the use of a language. Moreover, the findings of this research also support the fact that a language keeps evolving in different contexts leading to the development of different varieties of the language. However, the researchers have studied comparatively many varieties of Englishes, but this research investigates the distinguishing features of Pakistani Standard English employing secondary data from Dawn e-newspaper. Additionally, the researchers have also qualitatively codified the data into broader themes. The findings of this research will help readers in understanding the role of a cultural context in developing a new variety of a language. Consequently, they will be able to carry out further research in the field of World Englishes. Hence, this research is a systematic investigation of Pakistani Standard English and its differentiating features.